Pengaruh Comparative Advantage Terhadap Daya Tarik Wisata Tugu Pahlawan Surabaya - Yoseph Agung Priyo Widodo (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This article is the result of research examining the effect of comparative advantage on the tourist attraction of the Surabaya Heroes Monument. The aim is to also know what indicators attract tourists to make tourist visits, so that they can optimize these components. The method used is quantitative using the SPSS application, the Non Propability Sampling test technique, namely Purposive Sampling, then the scale used is the Likert scale. Respondents numbered 55 people, namely visitors who visited the Surabaya City Heroes Monument more than twice. The research results showed that the highest Comparative Advantage was in cooperation and marketing ability at 3.87 and the lowest was in organizational ability, namely 3.08. The overall average value is 3.56, which means very good. The highest average value for tourist attractiveness in attractions was 3.79 and the lowest was for accessibility, namely 3.47. The overall average value is 3.64, which means very good.